Post 2015: enter the UN General Assembly: harnessing Sustainable Development Goals for an ambitious global development agenda - Steffen Bauer; Ines Dombrowsky; Imme Scholz (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
With the wrapping up of the United Nations' Open Working Group (OWG) on Sustainable Development Goals (SDGs) at the end of July 2014, the international process towards the adoption of universal sustainable development goals has entered its decisive phase. Established in the wake of the 2012 Rio+20 summit on sustainable development, the OWG has arguably fulfilled its task by tabling a substantive proposal that represents an integrated indivisible set of global priorities for sustainable development with aspi¬rational global targets. Crucially, the OWG's proposal re¬flects the global level of ambition as well as attention to national circumstances. It is now up to UN Secretary-General Ban Ki-Moon and, ultimately, the UN General Assembly (UNGA) to follow up on the OWG proposal and to foster consensus at the global level. Concomitantly, the SDGs also need to be anchored within an institutional system that facilitates progressive implementation and ensures accountability. The OWG has come a long way in paving the ground, but deliberations will continue before the UN General Assembly eventually adopts a consolidated set of SDGs in 2015. This defines the political space to promote improvements as the international community strives for a set of goals that is pragmatic enough to ensure broad ownership across the North-South divide and ambitious enough to actually make a difference vis-à-vis business as usual. Four issues deserve particular attention from policymakers and negotiators: Negotiators should not let themselves be diverted by the quest for a smaller number of goals. The total number of SDGs is of little concern for each SDG to deliver on its promises. The substance and the feasibility of individual targets matters, not the memorability of the set of goals as such. A consolidated set of SDGs should further emphasise the potential of integrated approaches wherever this is reasonable, for example with regard to targets relating to water, food security and energy provision. The goals tabled by the OWG could do better to overcome the silo approach that has characterised the Millennium Development Goals (MDGs). The goals need to be ambitious both in terms of substantive targets and in terms of sharing the burdens of implementation in the envisaged 'global partnership'. Now is the time to specify who is expected to be doing what, by when, and with which means. The goals are supposed to be universal and hence need to be relevant and fair for developed countries and developing countries, as well as within all countries. The notion of 'leaving no one behind' should be reflected more consistently across the eventual set of goals. This briefing paper elaborates on these priorities as it critically appraises the outcome of the OWG with a view to forthcoming sessions of the UN General Assembly. It also identifies challenges for implementation, notably regard¬ing the responsibilities of Germany and the European Union. It concludes that all countries will be well advised to devise national road maps that facilitate the incorporation of the SDGs into domestic policy. These should be fashioned in a manner that is in itself aspiring and flexible enough to allow for progressive adjustment as the global partnership for sustainable development evolves beyond 2015.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Agenda 2030